2014
DOI: 10.1177/0361684314537997
|View full text |Cite
|
Sign up to set email alerts
|

You, Me, or Her

Abstract: We examined how university leaders described what and who needed to change in order to increase the representation of female faculty in science, technology, engineering, and math (STEM) departments. Thirty-one (28 men and 3 women) STEM departmental chairs and deans at a large, public university participated in semi-structured interviews. Data were examined using both qualitative and quantitative procedures. Analysis focused on participants' descriptions of responsibility for changes related to gender equity. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 62 publications
0
24
0
Order By: Relevance
“…As has been done in past qualitative work utilizing inductive thematic content analysis (McClelland and Holland, 2015; Moss-Racusin et al, 2015), the expansive body of research on culture in computer science, particularly related to academia, has been used to guide the analysis such that specific thematic categories arose organically from the data. Using the cloud-based software app Dedoose, two members of the research team were responsible for independently coding the data, beginning with a pilot test on a sub-sample of the data.…”
Section: Methodsmentioning
confidence: 99%
“…As has been done in past qualitative work utilizing inductive thematic content analysis (McClelland and Holland, 2015; Moss-Racusin et al, 2015), the expansive body of research on culture in computer science, particularly related to academia, has been used to guide the analysis such that specific thematic categories arose organically from the data. Using the cloud-based software app Dedoose, two members of the research team were responsible for independently coding the data, beginning with a pilot test on a sub-sample of the data.…”
Section: Methodsmentioning
confidence: 99%
“…In both local and in other (as an external reviewer) tenure and promotion cases, I tried to acknowledge and accentuate the (often unsung) work and importance of the candidate's mentoring of students as co-authors and coreviewers of journal articles. Even more effective is the work of researchers who turn their skills to collaborate on Status of Women reports within their institution (see Gaughan & Su, 2012, for a review), to document inequities (e.g., MIT Status of Women Report, 1999), and to systematically examine the attitudes and behaviors of gatekeepers such as academic administrators (like Shield's project; also see McClelland & Holland, 2015).…”
Section: Challenging the Academic Hierarchymentioning
confidence: 99%
“…In a separate study of academic leaders, researchers found that when leaders felt personally responsible for creating diversity change, they not only reflected on the personal ways in which they needed to change, but encouraged their subordinates (men) to do the same as they worked collectively toward more equitable policies and practices. On the other hand, when leaders expressed low personal responsibility for increasing gender diversity, they did not initiate meaningful change and perceived that the onus of responsibility for such changes lied with women faculty (McClelland & Holland, 2014).…”
Section: Synopsis Of the Gender Inequity Problem In Stemmentioning
confidence: 99%
“…The reasons for this discrepancy are debated and range from assertions that women are just not as interested as men are in fields like the hard sciences (i.e. physics, math, engineering, computer science), to women who choose an academic career in the hard sciences often depart from the field to start a family (Bailyn, 2003;Blickenstaff, 2005;Maranto & Griffin, 2011;McClelland & Holland, 2014) Bailyn (2003) calls for a revision of conceptions of gender equity which are satisfied with equality of opportunity for women based on male-constructed norms and/or conceptions of gender equity which tout the establishment of inclusionary policies and practices which acknowledge "an academic's outside life" as evidence gender equity has been achieved. Instead, she maintains that an "ideal image of gender equity," not only legitimates "the private sphere of family, community, and other personal involvements," but equalizes "the value placed on economic and noneconomic activity" (p. 140).…”
Section: Gender Equity In the Academymentioning
confidence: 99%
See 1 more Smart Citation